2016
DOI: 10.1097/md.0000000000005186
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic transforaminal lumbar spinal canal decompression for lumbar spinal stenosis

Abstract: This study aimed to evaluate the safety and curative effect of percutaneous endoscopic transforaminal lumbar spinal canal decompression in the treatment of lumbar spinal stenosis.This retrospective study recruited 64 patients with lumbar spinal stenosis who underwent percutaneous endoscopic lumbar spinal canal decompression via surgical approach of posterolateral intervertebral foramen. The postoperation neurological function and pain status were evaluated by the visual analog scale (VAS) score of pain and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 21 publications
2
21
0
1
Order By: Relevance
“…Some authors have also reported good clinical results of endoscopic lumbar unilateral decompression for lateral recess stenosis through transforaminal approach [17,21,[28][29]. However, transforaminal unilateral decompression is often insu cient for CLSS.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have also reported good clinical results of endoscopic lumbar unilateral decompression for lateral recess stenosis through transforaminal approach [17,21,[28][29]. However, transforaminal unilateral decompression is often insu cient for CLSS.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported satisfactory results of patients with LRS following TESSYS with endoscopic drill system [12,22]. In order to achieve effective dorsal decompression of LRS , the distance from the midline to the skin entry point is farther than that of a typical transforaminal approach in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…All these causes pressurize the nerve root which leads to the disease. The purpose of intervention in this disease is to decrease the pressure and tension applied on the nerve by removing the source of pressure [6][7][8][9][10][11][12]. The percutaneous foraminotomy introduced in this case report is a newly developed minimally invasive device that reduces pressure on the nerve root as well as the blood vessels in the neural canal.…”
Section: Discussionmentioning
confidence: 99%